Composition of subsurface bottom sediments from the southwest Barents Sea. - Lavrushin, Yu I; Spiridonov, M A; Sakharov, B A; Golubev, Yu K; Tkachenko, V A; Rybalko, A E (PANGAEA, 1984)
Structure and composition of sub-surface bottom sediments from the southwest Barents Sea have been under study. The study has revealed heterogeneity of sediment structure resulted from temporal irregularity and variability of sedimentation processes. The study of the heavy minerals from 0.1-0.01 mm grain size fraction has shown prevalence of green hornblende, epidote, garnet, and ilmenite in all types of sediments; these minerals are the basis of terrigenous-mineralogical province. At the same time in different areas local terrigenous-mineralogical associations have been identified. Clay mineral composition of in the sediments was quite uniform: biotite, chlorite, hydromica, smectite. Despite this, a number of features indicating initial stages of clay mineral transformation has been identified. Differences in material composition and structure of the studied sediments are associated with rapid change in paleogeographic situation on the land - ice cover melting on the Kola Peninsula and subsequent Holocene climatic situation.
Relative contents of heavy minerals in 0.100-0.010 mm grain size fraction from bottom sediments of the southwest Barents Sea
Keywords: Actinolite; Aegirine; Aegirine-augite; Amphibole group minerals; Apatite; Archive of Ocean Data; ARCOD; Augite; Biotite; Carbonates; Chlorite; Counting 10-100 µm fraction; DEPTH, sediment/rock; Disthene; Epidote; Ferrohornblende; Garnet; GC; Glaucophane; Gravity corer; Heavy minerals; Hematite, Fe2O3; Hornblende, brown; Hornblende, green; Ilmenite; Leucoxene; Limonite; LSSGTR-322; LSSGTR-323; LSSGTR-324; LSSGTR-325; LSSGTR-327; LSSGTR-328; LSSGTR-329; LSSGTR-331; Magnetite; Muscovite; Nonidentified, altered, heavy; Ore; Pyrite, FeS2; Pyroxene group minerals; Rutile; Sediment type; Separation with use of heavy (2.9) liquid; Sillimanite; Southwest Barents Sea; Sphene; Staurolite; Tourmaline; Zircon; Zoisite